Identifikasi Tumbuhan Obat di Kecamatan Gunungsari sebagai Bahan Penyusunan Booklet - Amelia Sapitri; Akhmad Sukri; Ismail Efendi; Agus Muliadi (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Traditional medicinal plants represent a vital component of local wisdom passed down through generations, yet most remain scientifically undocumented. Unlike previous studies on medicinal plant identification that typically concluded at the species inventory stage, this research offers a novel contribution by integrating findings on local medicinal plants into a scientifically validated booklet, thereby enabling its immediate use as an educational resource. This study aimed to identify the medicinal plant species utilized by the community in Gunungsari District, West Lombok Regency, and to assess the validity of the booklet developed based on these findings. An exploratory descriptive method employing both qualitative and quantitative approaches was used. Data were collected from eight villages randomly selected from the sixteen villages in Gunungsari District (Bukit Tinggi, Penimbung, Mekarsari, Jeringo, Ranjok, Kekait, Kekeri, and Taman Sari) through field observations, structured interviews with eight traditional healers (belian) representing each village, and a literature review. The results revealed that the community utilizes 29 species of medicinal plants from various families. The most frequently used plant parts were leaves (48%), followed by rhizomes (28%), flowers (14%), fruits (10%), and stems and roots (3% each). The dominant preparation method was a combination of techniques (62.07%), followed by boiling (34.48%) and pounding (3.45%); the Zingiberaceae family was the most represented group. The developed booklet was deemed highly valid by three validators a subject matter expert, a media expert, and a linguist achieving an average validity score of 88.17%, making it suitable for use as a local wisdom-based educational resource for the community and learners. From a scientific perspective, the results of this study provide baseline ethnobotanical data on medicinal plants in Gunungsari District; these data can serve as a reference for further phytochemical and pharmacological research and as a model for developing educational materials based on local wisdom that can be implemented in other regions.